2009
DOI: 10.1123/pes.21.4.400
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Physical Activity Preferences in Latino and White Preadolescents

Abstract: The purpose of this study was to assess physical activity preferences (PAP) in preadolescent children. 191 Latino and White children (M = 11.9, SD = +/- 0.7) participated. Demographic, anthropometric, and PAP measures were employed. Both Latino and White children reported water play, basketball, and bicycling as their most preferred activities while indoor chores were least preferred. Compared with Latino, White children reported a higher preference for baseball/softball. Exploratory factor analysis of PAP mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…It is interesting that the preferences were not related to abdominal adiposity. This finding was in contrast to previous studies that found BMI – as a measure of child body composition – was associated with children's PA preferences . This supports our hypothesis that BMI might have served as a proxy for CRF and, by extension, motor skills.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…It is interesting that the preferences were not related to abdominal adiposity. This finding was in contrast to previous studies that found BMI – as a measure of child body composition – was associated with children's PA preferences . This supports our hypothesis that BMI might have served as a proxy for CRF and, by extension, motor skills.…”
Section: Discussionsupporting
confidence: 70%
“…The limited number of studies that have investigated children's PA preferences have identified four associated variables, namely ethnicity, gender, age and body mass index (BMI). However, these studies were based on relatively simple comparisons within special populations and included relativity few children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One previous study examining whether children in after-school programs were meeting state and national physical activity guidelines found that African American children were more active than their white, non-Hispanic counterparts (Beets et al, 2010). Activity preferences differ between girls of different races/ethnicities (Olvera et al, 2009; Grieser, Vu, Bedimo-Rung, and Neumark-Sztainer, 2006; Dowda et al, 2004), and the after-school programs in this study may have focused on activities that appealed more to minority girls than white girls. In addition, social norms for minority girls may differ between the after-school program and the home environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, Sallis et al found that amenities such as basketball courts/hoops in school settings, were associated with more physical activity, especially for boys. 40 Basketball is a common activity among boys and girls in the U.S., 41,42 and is associated with high levels of physical activity, especially during practice. 43 In non-American contexts, other items, such as soccer (football) goals, might represent accessible and popular sports equipment that promotes physical activity near the home.…”
Section: Discussionmentioning
confidence: 99%